Posttraumatic checkrein deformity following isolated Lauge–Hansen pronation external rotation stage IV malleolar fracture—a case report and literature review - Chen, Wen-tao; Liu, Zhen-yu; Wang, Bao-jun (Frontiers in Surgery, 2023)
The checkrein deformity is characterized by flexion contracture of the interphalangeal joint and extension contracture of the metatarsophalangeal joint. It is a rare condition occurring after lower extremity trauma, especially malleolar fracture. Little is known about possible cause and therapeutic strategy. This unique case presents a 20-year-old male patient with diagnosis of the checkrein deformity secondary to open reduction and internal fixation of Lauge-Hansen pronation external rotation stage IV malleolar fracture. After performing a detailed physical examination, radiographic evaluation and ultrasonography, open exploration was performed to remove the hardware and correct the deformity with sole tenolysis of the flexor hallucis longus. In the 4-month follow-up, no recurrence of the checkrein deformity was observed. This deformity was caused by FHL adhesion. Interosseous membrane injury and fibular fracture together with local hematomas increases the risk of FHL adhesion. Open exploration and tenolysis of the FHL are feasible options to correct the checkrein deformity.